Analysis of Sino-Indian trade and tourism as the base for the revival of their partnership - Sharma, Amit; Lu, Haiping; Kusdarjito, Cungki (Farabi Journal of Social Sciences, 2021)
India and China are among the fastest growing emerging market economies; and have experienced rapid rise in trade and tourism in recent years. This guided the choice of the two countries for in-depth analysis. This is a rare study which empirically explores the association of tourism, with trade, and growth. Tourism has multi-dimensional ramifications relating to dissemination of innovation, technology, organization, and managerial techniques. These in turn promote productivity and propel growth in countries. Econometric models are used to determine the degree and direction of causality between Sino-Indian tourism, trade and GNP. The study has used detailed theoretical background for specifying the relationship between the core variables of the study. The Random Walk Model (RWM) stands rejected in relation to time series data of Sino-Indian tourism and trade in the study. The study has found Outbound/Inbound Sino-Indian tourism to be a direct function of Sino-Indian trade whereas trade emerges as a function of GNP. However, the ratio of Sino-Indian tourism to India’s world tourism is inversely related to the ratio of Sino-Indian trade to India’s world trade because Sino-Indian tourism grows less than proportionately than Sino-Indian trade relative to India’s world trade. This implies that Sino-Indian tourism and trade remains below its potential and has great prospects for growth. Keywords: Indo-Chinese, tourism, trade, GNP, RWM, econometric-modeling